KEWENANGAN KEPALA DAERAH TERHADAP BADAN USAHA MILIK DAERAH DITINJAU DARI HUKUM ADMINISTRASI NEGARA - Agustina, Enny (Solusi, 2020)
The research objective was to analyze and explain the authority of the regional head towards the state-owned body in terms of state administrative law. The research method of this paper uses a normative juridical research method. Research results: The state is an organization of power because in the country we always meet the centers of power, both in the superstructure (incarnated in political institutions and state institutions) and infrastructure which includes political parties, interest groups, pressure groups, political communication tools. This study uses normative estimation so that the sources used come from the literature, literature. This study discusses the authority of the Regional Head towards Regional Owned Enterprises. The results obtained from the study are Regional Owned Enterprises in the form of Regional Companies formed through Regional Regulations based on Law No.5 of 1962 concerning Regional Companies. After the Regional Company has its form as a Limited Liability Company, the rules concerning the Limited Liability Company apply to him with shares owned by the region in whole or in part. The Regional Head as the personification of the Regional Government is the shareholder in the Regional Owned Enterprise. All authorities possessed by regional heads are limited in the scope of authority as shareholders.